Reduced Pain, Shorter Hospital Stay And Early Return To Work In Pcnl: Comparative Study On Outcome Of Pcnl Versus Open Surgery In The Treatment Of Large Renal Calculi (Bangladesh Journal of Urology, 2020)
Objective: To compare the outcome of PCNL & open surgery in the treatment of large renal calculi by assesing the amount of analgesia required to relief pain, mean hospital stay, & convalescence period.Materials & Methods: : This comparative study in during 80 patients diagnosed with kidney stone disease admitted in the NIKDU during the period of Jan’ to Dec’2009. They were divided conveniently into two groups. Intervention was done in the formPCNL(40) and open surgery (40). Clinical outcome like, duration of surgery, postoperative hospital stay,doses of narcotic analgesia required to relief pain and convalescence periodwere reviewed. In complete follow up 9 patients were missed in PCNL group resulting in 31 patients. There was no significant difference in preoperative variables such as age,sex, stone size in cm, stone number- single/multiple and stag horn Stone.Results : There were statistically significant difference in the parameters between the groups,( PCNL vs open surgery [mean ± SD]): duration of operation (min), 97.90 ± 24.89 vs 136.62 ± 23.54, postoperative hospital stay (days) ,4.77 ± 3.98 vs 9.55 ± 3.65, mean time return to work (days) , 3.09 ± 1.21vs 6.25 ± 1.53, ( p value is 2 doses vs 27 patient required 3 or >3 doses ), p value is